Effect of exclusive breast-feeding on the linear growth of children aged 24-36 months in Bandung's urban slum area - Nenden Ismawaty; Julistio Djais; Herry Garna (Paediatrica Indonesiana, 2008)
Background Breast milk is an ideal nutrition source for infantsbecause of its balanced composition, naturally adjusted toinfants' need for growth and without any expenses. However,low education mothers living in slum areas are ignorant towardsinformations about the importance of exclusive breast-feeding.Objective To observe the effects of exclusive breast-feeding onlinear growth of children aged 24-36 months in urban slumsarea.Methods A cross-sectional study was carried out on 343children consisted of 188 exclusively breastfed infants and 155nonexclusively breastfed infants in Puskesmas Cigondewaharea on August to September 2007. Anthropometricmeasurements were performed to obtain linear growth status.Data were analyzed by using odd ratio (OR). The first step wasperformed univariately to assess the effect of data variables.Henceforth, factors which significantly influence the growthwill be assesed by multivariate calculation.Results Normal linear growth status was found in 109 (66.1%)exclusively breastfed compared with 56 (33.9%) nonexclusivelybreastfed children. Univariate analyzes showed that factorsthat influenced children normal linear growth were exclusivebreast-feeding (OR: 2.44; 95%CI: 1.58;3.78), industrial productporridge as complementary food (OR: 1.65; 95%CI: 1.00;2.72),and frequency of illnesses <6x/year (OR: 1.57; 95%CI: 1.02;2.42).The result of multinomial logistic regression analyzes showed thatexclusive breast-feeding became the only factor that influencechildren linear growth (OR: 2.254; 95%CI: 1.438;3.533).Conclusion Exclusive breast-feeding has significant positive effect onlinear growth of children.